Simultaneous Allocation of DG and DSTATCOM Using Whale Optimization Algorithm - Yuvaraj T.; Devabalaji K.R.; Thanikanti S.B. (Springer, 2023)
This paper proposed a new methodology based on nature-enthused meta-heuristic optimization algorithm named as whale optimization algorithm (WOA), which can significantly envisage problems for simultaneous allocation of distributed generation (DG) and Distribution STATic COMpensator (DSTATCOM) in the radial distribution systems (RDS). In the proposed method, optimal locations and sizing of the DG and DSTATCOM can be determined by loss sensitivity factor and WOA, respectively. The objective function of the proposed method is to minimize the systems total power losses and total operating cost of DG and DSTATCOM. The proposed method is applied to well-known IEEE 33-bus and large 136-bus RDS. The attained simulation results and comparison of different cases considered leads to allocation of DG and DSTATCOM combination resulting in significant power loss reduction with good voltage profile enhancement. 2019, Shiraz University.